PENGARUH ISLAMIC GOVERNANCE SCORE, LEVERAGE, PROFITABILITAS, DAN SIZE TERHADAP ISLAMIC SOCIAL REPORTING INDEX PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2012-2016 - Fatin Nabilah; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine the influence of Islamic Governance Score(IGS), Leverage (DAR), Profitability (ROA), and Size of Islamic Social ReportingIndex at Sharia Commercial Bank registered in the Financial Services Authority(OJK) period 2012-2016. The type of research used is quantitative. This researchuses purposive sampling technique. The population used in this study were 13companies and produced 7 sample companies based on predetermined criteria forone year, resulting in 35 sample data of the company for five years for the period2012-2016. By using multiple linear regression analysis, the result of thisresearch proves that Islamic Governance Score (IGS), Leverage (DAR),Profitability (ROA), and Size influence to Islamic Social Reporting Index. IslamicGovernance Score (IGS) has no effect on Islamic Social Reporting Index.Leverage (DAR) has a negative effect on Islamic Social Reporting Index. WhileProfitability (ROA) and Size have a significant positive effect on Islamic SocialReporting Index.Keywords : Islamic Governance Score, Leverage, Profitability, Size, IslamicSocial Reporting Index